Development and Validation of a Scoring System for Predicting Complications of Pancreatitis in Patients with Post Endoscopic Retrograde Cholangiopancreatography - Melatunan, Leonard A.; Mambu, Toar D. B.; Tendean, Michael; Langi, Fredrik G. L. (e-CliniC, 2024)
Abstract: Post ERCP pancreatitis (PEP) is the most common complication of endoscopic retrograde cholangiopancreatography (ERCP) with significant morbidity and mortality rates. Several factors are associated with the occurrence of PEP. There are several methods available to predict such complications, however, they are not yet valid and need some improvement. This study aimed to obtain a scoring system to predict the incidence of post ERCP pancreatitis. This was a retrospective study using medical records of patients who underwent ERCP at Prof. Dr. R. D. Kandou Hospital from 2017 to 2023. The results obtained 372 patients as samples. Gender, previous history of ERCP, cannulation attempt ≥5 times, pancreatogram, double wire technique, EPBD, and pancreatic duct stent failure were independently associated with PEP and included in the model, which achieved AUC 96.7%, sensitivity 95.0% and specificity 89.8%. In conclusion, a predictive scoring system to assess the incidence of post ERCP pancreatitis (PEP) using seven risk factors related to patient, procedure, operator, and technique is used to aid early identification of PEP and therapeutic intervention. This scoring system is simple and easy to use, and has high area under curve (AUC), sensitivity, and specificity. Keywords: endoscopic retrograde cholangiopancreatography (ERCP); post ERCP pancreatitis; scoring system